Analysis of the Quality and Financial Viability of Hard Candy Innovation Products with the Addition of Gambir Catechins (Uncaria Gambir Roxb) - Maryam Maryam; Tosty Maylangi Sitorus; Hartami Dewi; Rizki Fadhillah Lubis (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2022)
Developing hard candy as a functional food with antioxidants and antibacterial properties derived from natural ingredients will do. By analyzing the formulation of innovations and analysis of the financial viability of hard candy products with the addition of gambir catechins, it is expected to provide information to stakeholders related to the development of hard candy innovation products with the addition of gambir catechins (Uncaria gambir Roxb.). The results of the analysis of organoleptic tests, obtaining formulas 17, 8, 18, 4, 7 hard candy had the rating respondents liked very much (4-5). Then conduct a quality test based on SNI hard candy 3547.1:2008 on products that have the criteria of organoleptic test results. Results from SNI hard candy test 3547.1:2008, the product met the standard requirements of SNI 3547.1:2008 products. When compared to hard candy products on the market with an average selling price of around Rp. 333.33, the hard candy products in this study can compete, especially strawberry variants. On a production scale of at least, 10 kg of hard candy HPP can compete with other products, where the hard candy in this study has a high added value antioxidant and has antibacterial properties useful for the health of consumers.